PENGEMBANGAN E-MODUL MODEL PEMBELAJARAN BERBASIS KETERAMPILAN ABAD 21 - Revita Yuni; Putri Kemala Dewi Lubis; Putri Sari MJ Silaban; Roza Thohiri; Elsa Aurel Agustine Situmorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educators can create innovative teaching materials by utilizing engaging information technology that can be carried and read anytime and anywhere. Moreover, students are now synonymous with the gadgets (smartphones) they often carry. In addition to innovative teaching materials based on information technology, teaching materials that can provide students with a more comprehensive understanding are also needed. 21st-century learning focuses on technology integration and the development of essential skills such as critical thinking, creativity, communication, and collaboration (4Cs), as well as contextual and problem-oriented learning. Developing 21st-century skills plays a vital role in preparing students to face the complex challenges of the modern era. Education is expected to produce individuals who not only excel academically but also possess the ability to adapt, think critically, solve problems, and innovate. This study aims to develop an e-module based on a learning model that integrates 21st-century skills in economics learning, with a high level of validity, practicality, and effectiveness. This research is a research and development (R&D) that adapts the five stages in the ADDIE model, namely analysis, design, development, implementation, and evaluation. The implementation of the development research includes (a) defining problems and needs analysis; (b) planning product design and (c) Implementation and evaluation of the e-module learning model based on 21st-century skills. The subjects in this study were sixth-semester students from the Economics Education study program. This study employed data analysis techniques that included validity, practicality, and effectiveness tests. The e-module validation process was conducted by two validator experts: a material expert and a design expert. Based on the research results, the feasibility test obtained a very feasible category, while the practicality test, based on responses from the lecturer team (colleagues) and students, showed a very practical category. The effectiveness test results indicated that the implementation of the e-module with a 21st-century skills-based learning model was effective.